CERRM shared its expertise on bauxite mining - Ahmad Amirul Faiz, Ahmad Tajudin (Pejabat Naib Canselor, 2016)
A workshop aimed at enhancing awareness on issues relating to bauxite mining was organised by the International Maritime Organisation (IMO), with the cooperation of Ministry of Transport, Kuantan Port Authority (KPA) and Marine Department.